Phospholipidomics of bovine milk subjected to homogenization, thermal treatment and cold storage - Mou, Bolin; Yang, Wenqing; Song, Shuang; Shen, Cai; Panpipat, Worawan; Lai, Oi-Ming; Tan, Chin-Ping; Cheong, Ling-Zhi (Elsevier Ltd, 2022)
Milk processing technology disrupts milk fat globule membrane (MFGM) structures and decreases the phospholipid content in MFGM. The present study aimed to evaluate the effects of homogenization, thermal treatment, and cold storage on milk phospholipids. A total of 175 phospholipid molecular species were identified and quantified. Phosphatidylcholine was the most abundant phospholipid, and sphingomyelin accounted for only a small amount of phospholipid in bovine milk. In addition, a total of 37 plasmalogens (167.5 μg/mL) were identified in bovine milk with lysophosphatidylcholine plasmalogen being the most abundant. Processing technologies decreased the phospholipid content with both boiled and frozen milk demonstrating the highest reduction. Compared to raw milk, only 70% of phospholipid remained in frozen milk. Both S-plot and volcano-plot showed that heat treatment and subsequent cold storage decreased the phosphatidylserine and lysophospholipid contents. © 2022 Elsevier Ltd